1997
DOI: 10.1002/(sici)1096-8628(19970613)70:3<222::aid-ajmg3>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Familial translocation t(Y;15)(q12;p11) and de novo deletion of the Prader-Willi syndrome (PWS) critical region on 15q11-q13

Abstract: We describe a 17-year-old girl with mild Prader-Willi syndrome (PWS) due to 15q11-q13 deletion. The deletion occurred on a paternal chromosome 15 already involved in a translocation, t(Y;15)(q12;p11), the latter being present in five other, phenotypically normal individuals in three generations. This appears to be the first case of PWS in which the causative 15q11-q13 deletion occurred on a chromosome involved in a familial translocation, but with breakpoints considerably distal to those of the familial rearra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(36 reference statements)
0
9
0
1
Order By: Relevance
“…Although the t(Y;15)(q12;p11) is not known to be associated with PWS or AS, one report describes a child with PWS and a paternally derived der (15)t(Y;15)(q12;p11) [Eliez et al, 1997]. In this patient a de novo deletion of the PW syndrome critical region was found on the derivative chromosome 15 and it was proposed that the t(Y;15) may have predisposed to the generation of a microdeletion within the PWS region.…”
Section: Introductionmentioning
confidence: 95%
“…Although the t(Y;15)(q12;p11) is not known to be associated with PWS or AS, one report describes a child with PWS and a paternally derived der (15)t(Y;15)(q12;p11) [Eliez et al, 1997]. In this patient a de novo deletion of the PW syndrome critical region was found on the derivative chromosome 15 and it was proposed that the t(Y;15) may have predisposed to the generation of a microdeletion within the PWS region.…”
Section: Introductionmentioning
confidence: 95%
“…The deletion occurred on a paternally derived der (15)t(Y;15) (q12;p11). Alternatively, the association may have been fortuitous too [11]. It remains to be proven and further investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Some patients with PWS exhibit translocations involving chromosome 15 with deletion of the PWS region. Although the t(Y;15)(q12;p13) translocation was not involved in the PWS critical region (15q11–q13), two rare reports indicated that familial t(Y;15)(q12;p13) may result in predisposition to the generation of microdeletions within the PWS region or trisomy 15 [1011 ]. These studies suggested the possibility of an increased risk for abnormal offspring.…”
Section: Discussionmentioning
confidence: 99%